1996
DOI: 10.1128/iai.64.2.616-623.1996
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal immunoglobulin A derived from peritoneal B cells is encoded by both germ line and somatically mutated VH genes and is reactive with commensal bacteria

Abstract: We transferred peritoneal cells from BALB/c mice into C.B17 scid/scid mice. Six to eight months after injection, only cells with the B1 phenotype were retained in the spleens and peritoneal cavities of these mice. The lamina propria of the intestine contained many peritoneal, donor-derived, immunoglobulin A (IgA)-producing cells. The mesenteric lymph nodes of these mice were found to be a major site of proliferation and generation of IgA plasmablasts. We established eight IgA-producing hybridomas from the mese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(33 citation statements)
references
References 48 publications
3
30
0
Order By: Relevance
“…63 It is has also been suggested that B 1 class switch recombination may take place in the mesenteric lymph nodes. 48,64 We found that significant intestinal IgA only occurred in strains with some B-cell structures in the intestine, although these could be very disorganized, for example without follicular dendritic cells and germinal centres in mice deficient for the TNF receptor I. 42,65 Regardless of relative B 1 /B 2 contributions, the IgA response has a restricted V H repertoire of intestinal immunoglobulin a heavy chains in mouse 48 and man.…”
Section: Induction Of Iga Against Commensal Bacteriamentioning
confidence: 78%
“…63 It is has also been suggested that B 1 class switch recombination may take place in the mesenteric lymph nodes. 48,64 We found that significant intestinal IgA only occurred in strains with some B-cell structures in the intestine, although these could be very disorganized, for example without follicular dendritic cells and germinal centres in mice deficient for the TNF receptor I. 42,65 Regardless of relative B 1 /B 2 contributions, the IgA response has a restricted V H repertoire of intestinal immunoglobulin a heavy chains in mouse 48 and man.…”
Section: Induction Of Iga Against Commensal Bacteriamentioning
confidence: 78%
“…Bacteria 0165-2478/$ -see front matter © 2009 Elsevier B.V. All rights reserved. doi:10.1016/j.imlet.2009.03.013 Table 1 Examples of glycans as adhesion sites and receptors for selected bacteria and viruses that colonize, or infect, mucosal surfaces (adapted from [1,26,29,[60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]132] endogenous to the intestinal tract, oral cavity, and probably also the respiratory and genital tracts, are coated in vivo with S-IgA [9,13,17,[31][32][33][34][35][36][37][38][39] that limits their epithelial adherence and penetration, thereby confining them to the mucosal surfaces. Numerous models have demonstrated the role of antibodies, especially S-IgA, in protecting the intestinal and other mucosal tracts.…”
Section: Role Of Secretory Iga (S-iga) In Mucosal Immunitymentioning
confidence: 99%
“…This concept, of paramount importance in IgA-mediated mucosal defense, prompts additional considerations. First, it has been shown that bacteria indigenous to the oral cavity and intestinal tract are coated in vivo with IgA [9,17,[31][32][33][34][35][36][37][38][39][79][80][81]. However, it is not known whether this coating depends on specific antibody-antigen or glycan-mediated interactions.…”
Section: Mechanisms Of S-iga-mediated Protectionmentioning
confidence: 99%
“…Although we believe that B1 cells can populate the gut with IgA plasmablasts and some of these make IgA that reacts with a particular pattern of microbial Ags (Bos et al, 1996), we have so far found little substantial evidence that indicates that these cells arise by specific Ag selection and stimulation to divide and/or differentiate into secretory plasma cells. Recently, Macpherson et al (2000) have shown that TCR (−/−) mice can exhibit an antimicrobial IgA response in the gut and that a complex radiation chimera seems to express a predominance of IgA plasmablasts with the allotype of the transferred, semipurified PeC B1 cells; no specific responses were measured in the latter case.…”
Section: Contribution Of Cells Of the B2 Versus B1 Lineage To Iga Promentioning
confidence: 94%